PENERAPAN KHIYAR DALAM TRANSAKSI JUAL BELI PERSPEKTIF HUKUM ISLAM (Studi Kasus di Pasar Haurgeulis Kabupaten Indramayu) - Madaniyyah, Kholishotul; Iswandi, Irvan; Fitri, Ahmad Asrof (Journal of Islamic Studies, 2023)
This research aims to find out how is the concept of khiyar implementation and the suitable of the implementation of khiyar at Haurgeulis Market with Islamic provisions .This research is a qualitative research. Data were collected through observation, interviews, and documentation. From the research results, it can be concluded that buy and sell practice in Haurgeulis Market has mostly used khiyar but khiyar concept is not well understood yet. The khiyar which is frequently used was khiyar majlis, khiyar ‘aib, and khiyar syarat. Khiyar ru’yah is still rarely used, while khiyar ta’yin is not used because it never happens. For the process of its implementation, it is still not fully in accordance with Islamic Shariah and in case of goods return period which must be according to the hadits in three days, while in Haurgeulis Market it can be more than three days or even there is no time limits.